2017
DOI: 10.15386/cjmed-686
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Treatment of Thrombosed Hemodialysis Arteriovenous Fistulas: Use of Thromboaspiration and Balloon Angioplasty

Abstract: BackgroundEndovascular strategies have been used to manage patients with thrombosed vascular access for hemodialysis. We analyzed primary success rate and patency rates of balloon angioplasty following mechanical thrombectomy for the treatment of thrombosed native arteriovenous fistulas.MethodsThis was a retrospective study of 24 patients with thrombosed native arteriovenous fistulas who were referred for treatment in the intervention unit of the Radiology Department. All patients had been performed percutaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
2
6
0
Order By: Relevance
“…In patients with associated thrombosis, success rates in the published literature range from 60% to 100%. [ 15 16 ] For thromboaspiration, Çildağ et al [ 11 ] reported a technical success rate of 83%, comparable to the results of present study (84.2%, n = 16).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In patients with associated thrombosis, success rates in the published literature range from 60% to 100%. [ 15 16 ] For thromboaspiration, Çildağ et al [ 11 ] reported a technical success rate of 83%, comparable to the results of present study (84.2%, n = 16).…”
Section: Discussionsupporting
confidence: 88%
“…The demographic profile of the study group showed male predominance (n = 29, 63.04%), with the most common decade of presentation being the sixth decade. [ 9 11 12 ] There was high prevalence of hypertension and diabetes in the study group, similar to the results of Al Gaby et al [ 12 ] and Hendawy et al . [ 4 ] This is compatible with the fact that diabetic nephropathy is the most common cause of chronic renal disease in the Indian population.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our study achieved a primary patency rate of 76.7% and a secondary patency rate of 93.3%, which was similar to or better than other reports in the literature. For example, Cildag et al evaluated thrombus aspiration followed by PTA, which achieved a technical success rate of 83% and primary and secondary patency rates of 40% to 55% at 6 and 12 months [15]. Kim et al used mechanical thrombectomy followed by PTA and reported a primary patency rate of 63% at 6 months [16].…”
Section: Discussionmentioning
confidence: 99%
“…Angioplasty alone can adequately restore the patency of a stenosed AVF [14], but the fistula thrombus must be treated first. Therefore, combining thrombus management and angioplasty may be effective for acutely thrombosed AVFs [15,16].…”
Section: Introductionmentioning
confidence: 99%